High-Efficiency Solar Cells Physics, Materials, and Devices - Wang, Xiaodong; Wang, Zhiming M. (Springer Series in Materials Science, 2014)
As part of the effort to increase the contribution of solar cells (photovoltaics) to our energy mix, this book addresses three main areas: making existing technology cheaper, promoting advanced technologies based on new architectural designs, and developing new materials to serve as light absorbers. Leading scientists throughout the world create a fundamental platform for knowledge sharing that combines the physics, materials, and device architectures of high-efficiency solar cells. While providing a comprehensive introduction to the field, the book highlights directions for further research, and is intended to stimulate readers' interest in the development of novel materials and technologies for solar energy applications. Offers comprehensive coverage of novel physics, materials, and devices for high-efficiency solar cells Provides the keys to understanding this critical area of renewable energy research Written by leading experts on each topic.